The Effect of Good Corporate Governance on Corporate Social Responsibility Disclosure on Jakarta Islamic Index - Erna Listyaningsih; Riska Dewi; Nur Baiti (School of Business, IPB University (SB-IPB), 2018)
The previous research results show various disclosures of the effects of Good Corporate Governance on Corporate Social Responsibility. The objective of this study was to examine the effects of Good Corporate Governance on the Corporate Social Responsibility disclosure to companies incorporated in the Jakarta Islamic Index. Proxies of Good Corporate Governance in this research include the managerial ownership, institutional ownership, foreign ownership, size of the independent commissioner board, size of the audit committee, and concentrated share ownership. The samples used in this study were companies registered in the Jakarta Islamic Index and had information on Good Corporate Governance and applied the disclosure of Corporate Social Responsibility during the period of 2013-2016. The total of the samples used consisted of 23 companies for the four year period. Multiple linear regression test was conducted to analyze whether Good Corporate Governance influenced the disclosure of Corporate Social Responsibility. The results of this study show that the variables that affect the disclosure of Corporate Social Responsibility are managerial ownership, institutional ownership, and foreign ownership. However, there are three variables that do not affect the disclosure of Corporate Social Responsibility that is the size of the independent commissioner board, size of the audit committee, and concentrated share ownership.Keywords: corporate social responsibility, good corporate governance, jakarta islamic index, regression